Investigation of the thermal and tribological performance of localized laser dispersed tool surfaces under hot stamping conditions - Schirdewahn, Stephan; Spranger, Felix; Hilgenberg, Kai; Merklein, Marion (Wear, 2021)
In the automotive industry, hot stamping has been established as a key technology for manufacturing safety-relevant car body components with high strength-to-weight ratio. However, hot stamping tools are stressed by cyclic thermo-mechanical loads, which leads to severe wear and high friction during the forming operation. Consequently, the quality of the parts, the durability of the tools and the efficiency of the process are negatively affected. Within the scope of this work, a promising approach named laser implantation process has been investigated for improving the tribological behavior of hot stamping tools. This technique enables the fabrication of highly wear resistant, separated and elevated micro-features by embedding hard ceramic particles into the tool via pulsed laser radiation. Hence, highly stressed tool areas can be modified, which influences the thermal and tribological interactions at the blank-die interface. To clarify these cause-effect relations, numerical simulations, quenching tests as well as tribological investigations have been conducted. In this context, laser-implanted tools reveal a significantly improved tribological performance while offering the possibility to adjust the thermal properties within hot stamping. Based on these results, a tailored tool modification can be pursued in future research work, in order to enhance the effectiveness of hot stamping tooling systems.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Friction; Hot stamping; Laser implantation; Surface structuring; Wear